2022
DOI: 10.1530/raf-22-0003
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from implementing the Australian National Action Plan for Endometriosis

Abstract: Endometriosis is a common yet under-recognised chronic disease with 1 in 9 (more than 830,000) women and those assigned female at birth diagnosed with endometriosis by the age of 44 years in Australia. In 2018 Australia was the first country to develop a roadmap and blueprint to tackle endometriosis in a nationwide, co-ordinated manner. This blueprint is outlined in the National Action Plan for Endometriosis (NAPE), created from a partnership between government, endometriosis experts and advocacy groups. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Endometriosis affects around one in nine Australian women and those assigned female at birth by the age of 44, 1 with at least 830 000 people in Australia likely to be affected. Despite a prevalence greater than diabetes, 2 and a cost of illness burden of over 9.5 billion AUD per year, 3 historically there has been a significant disparity in the amount of funding and resources allocated in comparison to other conditions with similar prevalence 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometriosis affects around one in nine Australian women and those assigned female at birth by the age of 44, 1 with at least 830 000 people in Australia likely to be affected. Despite a prevalence greater than diabetes, 2 and a cost of illness burden of over 9.5 billion AUD per year, 3 historically there has been a significant disparity in the amount of funding and resources allocated in comparison to other conditions with similar prevalence 4 …”
Section: Introductionmentioning
confidence: 99%
“…Despite a prevalence greater than diabetes, 2 and a cost of illness burden of over 9.5 billion AUD per year, 3 historically there has been a significant disparity in the amount of funding and resources allocated in comparison to other conditions with similar prevalence. 4 In 2018 the Australian government established a national action plan for endometriosis 5 with funding allocated for a variety of goals including increasing awareness, educational programs, and research into early detection, causes, and effective treatments. In addition, organisations such as Endometriosis Australia have also independently raised funds for endometriosis research.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 66.9% of women diagnosed with endometriosis stated they had at least one more medical condition, which means additional costs. These results are in parallel with the endometriosis burden in the USA and Australia [23,24]. Thus, provisions in healthcare policies, insurance coverage, and business plans are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…and it has been shown that coordinated efforts over time can substantially improve awareness among both the public and medical communities. 30,67,68 Such initiatives are always better served when quality data are available. Several important questions remain, especially in Asian populations.…”
Section: Discussionmentioning
confidence: 99%